1986
DOI: 10.1080/09553008614550991
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Thiyl Free Radicals with Oxygen: A Pulse Radiolysis Study

Abstract: A pulse radiolysis study of glutathione in aqueous solution at pH 5.5 containing N2O/O2 mixtures at various ratios indicates that oxygen rapidly adds to the thiyl glutathione radical yielding a transient absorption, with a maximum at 540 nm, whose characteristics appear to be compatible with assignment to the GSOO. radical. The reaction (Formula: see text) appears to be an equilibrium whose kinetic constants have been estimated (kf = 2.0 X 10(9) dm3 mol-1, kb = 6.2 X 10(5) s-1). Evidence for electron transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 4 publications
2
36
0
Order By: Relevance
“…4) provide evidence that a major overall pathway following direct excitation of GSNO is formation of GSSG. This is in agreement with previous studies of both GSNO decomposition (14) and pulse radiolysis of GSH (28). However, transient absorption spectroscopy has provided clear evidence that the mechanism does not simply involve homolysis and subsequent GS recombination.…”
Section: Hbo2supporting
confidence: 92%
See 1 more Smart Citation
“…4) provide evidence that a major overall pathway following direct excitation of GSNO is formation of GSSG. This is in agreement with previous studies of both GSNO decomposition (14) and pulse radiolysis of GSH (28). However, transient absorption spectroscopy has provided clear evidence that the mechanism does not simply involve homolysis and subsequent GS recombination.…”
Section: Hbo2supporting
confidence: 92%
“…In aerated or oxygen-saturated solutions the species GSOO, formed via reaction between G S and oxygen (Eq. 3) was detected by its characteristic absorption, peaking at 540 nm (28) (Fig. 3).…”
Section: Effect Of Oxygenmentioning
confidence: 99%
“…Although the sink hypothesis is kinetically and thermodynamically feasible [66], the sulfur centered radical can also react rapidly with oxygen producing species that could be competent for other, possibly damaging, reactions [67]. …”
Section: Can Free Radicals Be Efficiently Scavenged Under Biologicmentioning
confidence: 99%
“…However, RSOO' is not considered to be a good hydrogen abstractor (Sevilla et al 1990b) although one report suggests that it is an effective one-electron oxidant (Tamba et al 1986) . ESR work has shown that RSOO' is involved in a cyclic reaction sequence (reaction 6) which results in a highly reactive intermediate RS0 200' (Sevilla et al 1988(Sevilla et al , 1990a(Sevilla et al , 1990b .…”
Section: Rs' +Rsh Rssr' -+ H +mentioning
confidence: 98%
“…An alternative hypothesis is that the radical reactions of thiols in the presence of oxygen are the source of the COEE . In one model formation of thiol peroxyl radicals (RSOO') (Quintiliani 1983, 1986, Priitz and Monig 1987 in an equilibrium (reaction 5) (Tamba et al . 1986, Wardman 1988, has two consequences : (1) RSSR' -formation is suppressed as is any repair it may accomplish, and (2) RSOO' may itself lead to DNA inactivation (Priitz and .…”
Section: Rs' +Rsh Rssr' -+ H +mentioning
confidence: 98%